Language as a Bulwark of Resistance: A Sociolinguistic Analysis of Code-Switching and Identity Transformation in Black Maid Dialogue in Kathryn Stockett's Novel “The Help” - Anin Nur Azizah (CV. Green Publisher Indonesia, 2026)
Background: This study analyzes the phenomenon of code-switching between Standard English (SE) and African American Vernacular English (AAVE) in the dialogue of the black maid character in Kathryn Stockett's novel The Help. Objective: The main focus of this study is to reveal how language use functions as an indicator of the transformation of character identity from a submissive position to one of resistance to racial oppression in 1960s Mississippi. Methods: Using a descriptive qualitative sociolinguistic approach, data from Aibileen Clark and Minny Jackson were collected through a listening-note technique and analyzed based on the interlocutors and narrative stages. The data were classified into three phases: a submissive phase characterized by SE accommodation for self-protection, a transition phase through intra-sentential switching negotiation, and a resistance phase that emphasized the use of strong AAVE features. Results: The research findings suggest that linguistic features such as zero copulas and double negatives are not merely dialectal variations, but rather instruments of symbolic power struggles and assertions of self-sovereignty. This shift in code-switching patterns reflects the evolution of the servants' collective identity from muted servants to individuals who boldly challenge racial and gender hierarchies. Conclusion: This study fills the gap in previous studies by integrating the analysis of linguistic features with the psychosocial dynamics of characters in the context of segregation.